Evaluation of immune microenvironment in IgG4-related sialadenitis: Immune Microenvironment in IgG4-Related Sialadenitis - Hu, Qing; Zhou, Peng; Yan, Yixuan; Huang, Qun (Cellular and Molecular Biology, 2023)
IgG4-related sialadenitis is a systemic autoimmune disease that can lead to fibro-inflammatory conditions. This study aims to investigate the immune microenvironment and potential signaling pathways associated with IgG4-related sialadenitis. Datasets related to IgG4-related sialadenitis were retrieved from the GEO database. Immune cell infiltration analysis was conducted using the Cell-type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT) method. Differentially immune-related expressed genes (DIEG) and immune-related functional enrichment were identified. Moreover, potential treatment targets for IgG4-related sialadenitis were predicted using The Connectivity Map. Only two datasets from GEO were included for further analysis. The CIBERSORT results indicated dominant immune cell populations in IgG4-related sialadenitis, including CD8+ T cells, resting NK cells, monocytes, and naïve B cells in peripheral blood mononuclear cells. Additionally, high abundance of plasma cells was observed in labial salivary gland tissues. Furthermore, a total of 42 DIEGs were identified, with tumor necrosis factor (TNF) signaling via the NF-Kappa B signaling pathway and the p53 signaling pathway being highly enriched. Autophagy inhibitors and DNA topoisomerase inhibitors were strongly associated with potential targets for the treatment of IgG4-related sialadenitis (P<0.05). This study reveals altered immune microenvironment in peripheral blood mononuclear cells and labial salivary gland tissues in IgG4-related sialadenitis. Autophagy inhibitors and DNA topoisomerase inhibitors show promise as potential targets for treating IgG4-related sialadenitis, providing a novel therapeutic strategy for this disease.